Canino retido com risco de fratura mandibular: Relato de um caso e revisão da literatura (Research, Society and Development, 2024)
Retained teeth are those that have not erupted in the mouth in the expected time due to the presence of an unquestionable obstacle, regardless of age, degree of root formation and whether the crown is inside or outside the bone, compromising tooth mobility, esthetics and functional outcomes. The mandibular canine shows an unusual tendency for retention-impaction; therefore, this rare dental condition can present significant challenges for both orthodontists and maxillofacial surgeons. The objective is to present a case report of the surgical extraction of an impacted-retained left mandibular canine at the level of the basal mandibular border, as well as a review of the literature on this rare condition. Case report: Surgical extraction of a retained left mandibular canine at the level of the basal mandibular border was performed in a 13-year-old male patient, who was fitted with osteosynthesis plates as a preventive material due to the risk of fracture. Conclusion: The presence of a retained-impacted mandibular canine is an infrequent event, clearly observed with current radiographic techniques, the best being CBCT (computed beam tomography). Its early diagnosis is essential for an adequate treatment planning between specialists to determine its treatment, either orthodontic traction or surgical exodontia, ending with the use of osteosynthesis material as a preventive measure, providing adequate support at the mandibular level, thus avoiding fracture.